Finite-Time Stabilization of Uncertain Switched Positive Linear Systems with Time-Varying Delays. (11th January 2015) - Yu, Tianjian; Zhong, Yanke; Chen, Tefang; Chen, Chunyang
Abstract : This paper is concerned with finite-time stabilization (FTS) analysis for a class of uncertain switched positive linear systems with time-varying delays. First, a new definition of finite-time boundedness (FTB) is introduced for switched positive system. This definition can simplify FTS analysis. Taking interval and polytopic uncertainties into account, a robust state feedback controller is built such that the switched positive linear system is finite-time bounded. Finally, an example is employed to illustrate the validities of obtained results.